2017
DOI: 10.1371/journal.pone.0171515
|View full text |Cite
|
Sign up to set email alerts
|

Administration of bovine casein-derived peptide prevents cognitive decline in Alzheimer disease model mice

Abstract: There is a growing interest in identifying natural food ingredients that may serve to prevent dementia such as that due to Alzheimer disease (AD). Peptides derived from food proteins have been demonstrated to have various physiological activities such as a hypotensive action. Recent findings have indicated possible associations of hypertension with AD progression, and suggest that angiotensin converting enzyme (ACE) inhibitors with potential to pass through the blood brain barrier (BBB) may reduce the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 37 publications
3
56
0
1
Order By: Relevance
“…The establishment of AD model was conducted as protocol . The location of brain was verified in advance before the injection of Aβ 1‐42 : 2 mm posterior to bregma, 1.5 mm next to biparietal suture and 1 mm under skull.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of AD model was conducted as protocol . The location of brain was verified in advance before the injection of Aβ 1‐42 : 2 mm posterior to bregma, 1.5 mm next to biparietal suture and 1 mm under skull.…”
Section: Methodsmentioning
confidence: 99%
“…The establishment of AD model was conducted as protocol. [26] The location of brain was verified in advance before the injection of Ab 1-42 : 2 mm posterior to bregma, 1.5 mm next to biparietal suture and 1 mm under skull. Holes were drilled in the skull, and 410 pm Ab 1-42 (5 ll) was injected into the hole in 2 min and the syringe was removed 2 min after injection.…”
Section: Establishment Of Ad Modelmentioning
confidence: 99%
“…Min et al. () demonstrated that administration of milk peptide to AD model mice improved memory and suppressed the expression of inflammatory cytokines such as TNF‐α, marine collagen peptide (MCP)‐1, iNOS, p47 phox , and gp97 phox (Min et al., ). The 11 peptides obtained from porcine cerebral hydrolysate caused remarkable improvement of spatial memory and escape latency, in addition to significantly reducing the production of ROS and MDA compared to Pb 2± ‐exposed mice (Zou et al., ).…”
Section: Determination Of Neuroprotective Effect Of Peptides/hydrolysmentioning
confidence: 99%
“…Moreover, combinations of two or more enzymes may stimulate a higher degree of hydrolysis. Peptides with neuroprotective effects have been obtained from food proteins, including plant proteins (Chen et al., ; Jin et al., ; Li et al., ), meat proteins (Kim et al., ; Min et al., ; Wang et al., ), and marine proteins (Chai et al., ; Lin et al., ; Zhao et al., ). Li et al.…”
Section: Production Of Neuroprotective Peptidesmentioning
confidence: 99%
“…Neurotrophic peptides derived from bovine milk and its fermented products have received increasing attention. The administration of bovine casein hydrolysate prevented cognitive decline in AD model mice, with a reduction of inflammation and oxidative stress (Min et al, 2017). Furthermore, MKP, a tripeptide with greater blood-brain barrier (BBB) penetration, was one of the primary players in the prevention of cognitive impairment (Table 1).…”
Section: Cognitive Decline: Risk and Protective Factorsmentioning
confidence: 99%